Changes in peripheral oxytocin and vasopressin during a silent month-long Insight meditation retreat - Conklin, Quinn A.; Zanesco, Anthony P.; King, Brandon G.; Epel, Elissa S.; Saron, Clifford D. (Frontiers in Endocrinology, 2024)
Background: Given its putative roles in mediating prosocial behavior, attachment bonds, and stress physiology, oxytocin modulation has been hypothesized to be a biological correlate of the salubrious effects of meditation practice. Here we investigated the effects of a month-long silent meditation retreat on changes in oxytocin, and the related hormone and vasopressin, in relation to psychosocial changes in attachment style, anxiety, personality measures, and feelings of social connectedness with fellow meditators. Methods: Plasma oxytocin and vasopressin and selfreport questionnaires were measured in retreat participants (n = 28) at the beginning of, and 3 weeks into, a residential meditation retreat. Control participants (n = 34), who were similar in age, gender, and meditation experience, were also assessed across a 3-week interval. Linear mixed effects models were used to assess outcomes. Results: The retreat group showed a small but significant decrease in oxytocin compared to controls who showed no change. In the retreat group, higher openness to experience at Time 1 predicted greater reductions in oxytocin during the retreat, and lower oxytocin at Time 2 was related to stronger feelings of personal connection with fellow meditators. The changes in oxytocin were not related to attachment style or anxiety.Vasopressin decreased over time across both groups, suggesting no specific effect of retreat.These preliminary findings suggest that meditation training in the context of a silent residential retreat may reduce circulating levels of oxytocin. We interpret this finding from multiple theoretical perspectives, discussing key measurement limitations and proposing future study designs that may help to differentiate the effects of different meditation practices and contexts on oxytocin signaling.